Algorithms for Implementation of General Limit Representations of Generalized Inverses (Journal of Computational Mathematics, 2021)
In this paper we investigate three various algorithms for computation of generalized inverses which are contained in the limit expressions $\mathop{\rm lim}\limits_{z→0} V (DT + zI)^{-l} U$ and $\mathop{\rm lim}\limits_{z→0} V (DT + zI)^{-l} Z^e.$ These algorithms are extensions of the algorithms developed by various authors in [2], [3-4], [7-9], [16-18].